Fiscal Policy During Business Cycles in Developing Countries: The Case of Africa - Willi Leibfritz; Horst Rottmann (Center for Economic Studies and ifo Institute (CESifo), 2013)
Fiscal positions of African countries have improved significantly during the past decade. Higher economic growth, better terms of trade, improved donor support notably through debt relief and better control of expenditure contributed to this improvement. But at the same time government revenue and expenditure have become more volatile. The paper explores behaviour of government spending during business cycles. It finds that spending has on average been since 1980 broadly a-cyclical thus neither significantly aggravated nor mitigated cyclical fluctuations. But when comparing the two sub-periods before and after 2000 we find that before 2000 spending was on average (moderately) procyclical. While from 1980 to 2000 in almost two thirds of the 46 countries, which we examined, spending was procyclical this share declined to less than 40 percent after 2000 and in the majority of countries spending was a-cyclical or countercyclical. As more countries escaped from procyclicality Africa's resilience against external shocks improved. This also helped to better cope with the Great Recession of 2009.
Keywords: O11; O23; H30; H50; 330; developing countries; Africa; fiscal policy; business cycles